PSYCHOLOGICAL ANALYSIS OF FOLKLORE DISCOURSE AND IT’S ETIOLOGY - Abduvahabova Mahina, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Psycholinguistics has three main theoretical sources. The first is the psychological direction in linguistics. Linguists of past centuries wrote that language has been an activity of the spirit and a reflection of the culture of the people. At the same time, they noted that language contains not only a physical, but also a mental component, and thus belongs to the individual. Being a condition of communication and regulating human activity, language limits the knowledge of the world and makes it impossible to fully understand another person.